2021
DOI: 10.3389/fimmu.2021.706133
|View full text |Cite
|
Sign up to set email alerts
|

Combination Therapy of Mithramycin A and Immune Checkpoint Inhibitor for the Treatment of Colorectal Cancer in an Orthotopic Murine Model

Abstract: The axis of Programmed cell death-1 receptor (PD-1) with its ligand (PD-L1) plays a critical role in colorectal cancer (CRC) in escaping immune surveillance, and blocking this axis has been found to be effective in a subset of patients. Although blocking PD-L1 has been shown to be effective in 5–10% of patients, the majority of the cohorts show resistance to this checkpoint blockade (CB) therapy. Multiple factors assist in the growth of resistance to CB, among which T cell exhaustion and immunosuppressive effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Dual inhibition of PI3K/mTOR pathway combined with the microtubule targeting chemotherapy, paclitaxel, along with ICI, induced sustainable DC, T cell and NK responses, both locally in the TME and systemically [ 195 ]. Similar results targeting cancer stem cells with the polyketide antibiotic, Mithraymcin-A, and ICI in a CRC mouse model resulted in turning an immunologically cold tumor hot by increasing CD8+ T-cell infiltration and decreasing quantities of MDSC/TAMs in the TME [ 196 ].…”
Section: Basic Research In Cancer Immunologymentioning
confidence: 88%
“…Dual inhibition of PI3K/mTOR pathway combined with the microtubule targeting chemotherapy, paclitaxel, along with ICI, induced sustainable DC, T cell and NK responses, both locally in the TME and systemically [ 195 ]. Similar results targeting cancer stem cells with the polyketide antibiotic, Mithraymcin-A, and ICI in a CRC mouse model resulted in turning an immunologically cold tumor hot by increasing CD8+ T-cell infiltration and decreasing quantities of MDSC/TAMs in the TME [ 196 ].…”
Section: Basic Research In Cancer Immunologymentioning
confidence: 88%
“…Dutta R et al found that Mit-A can increase the expression of PD-L1 in CRC tissues, thereby increasing the drug sensitivity of anti-PD-L1 therapy. Combined treatment with Mit-A and anti-PD-L1 can increase the infiltration of CD8 + T cells and reduce the immunosuppressive Treg cells [ 292 ].…”
Section: Targeting Colorectal Cscsmentioning
confidence: 99%
“…Further exploring this information, the Bernstein lab identified that the reversal of the epigenetic silencing of SETDB1 activates tumor immunogenicity through the hypomethylation of H3K9 in the transposable elements that reside in the MHC peptidome [67,68]. The results of these studies indicate the high potential of SETDB1 inhibitors such as mithramycin in combination with immune checkpoint blockade therapy (ICT) [69].…”
Section: Epigenetic Modifiers In Immune Checkpoint Therapymentioning
confidence: 99%